Final Thoughts on Exampling - Barney G. Glaser (Grounded Theory Review: An International Journal)
The humble purpose of this book is to help novice researchers doing dissertation research to do good GT by emphasizing the learning of GT by example. There is much to learn as GT methods become developed in the literature every year. This book has focused so far on exampling GT from its inception in 1965 to the reader Methods of GT in 1994. In this chapter I will discuss exampling GT to 2007 when I put out a reader with Judith Holton of very well formulated GT papers. It was called the GT Seminar Reader. Since this reader was published in 2007 to today both method and substantive GT papers have burgeoned following the style and procedure examples given in this reader.